Talk vs chat-based radio: A case for distinction. (1st October 2016) - Ames, Kate
This article considers the differences between talk radio and chat-based radio as specific genres of radio programming in an attempt to address the very broad use of the term 'talk/talkback' radio in radio research. Chat-based programming is a term devised by Tolson in relation to television, but this article argues that the definition as applied to television is relevant to radio, particularly in a contemporary media environment where media boundaries are increasingly blurred. It examines the key concepts that define 'chat-based' programming as they apply to radio, which are an orientation to personal topics, the use of humour, and potential for transgression. The format is increasingly popular, particularly on commercial radio. This article investigates three key questions: (1) Is there a difference between chat-based and talk radio programming?; (2) Why does genre matter in radio studies?; and (3) What are the implications for defining an alternative genre of talk? It argues that talk radio and chat-based radio are distinct formats, but that chat-based programming can and does incorporate issue-based 'segments' to engage listeners. In arguing for the distinction, this article lays some foundations and raises questions for consideration in future analyses of radio talk.